Vellus hair follicle diseases - Hsing-San Yang; Wei-Ting Liu; Chao-Chun Yang; Gerd Plewig; Retno Danarti; WenChieh Chen (Wolters Kluwer Medknow Publications, 2024)
Human hair follicles are composed of vellus hair follicles (vHFs), sebaceous hair follicles, and terminal hair follicles (tHFs), which share histoanatomy, but differ in biophysiology, therefore are distinctive in clinical morbidities. vHFs are much less studied, and many issues remain to be clarified, such as the expression and regulation of androgen receptors, hair follicle stem cells, immune privilege, and microbiome. Hirsutism is an example of an endocrine disorder with the pathogenesis incompletely understood, especially in idiopathic hirsutism. Interactions between androgens and other hormones deserve special attention. Treatment is unstandardized, whereas combination of antiandrogens and laser shows promise. Keratosis pilaris, a keratinization disorder, lacks clarity in etiopathogenesis, impacting esthetics and therapeutic efficacy. Among the inflammatory disorders, perioral/periorbital dermatitis arises from vHFs irritation, categorized into papular, eczematous, and granulomatous forms. This necessitates varied differential diagnoses and therapeutic approaches. Follicular eczema, a variant of atopic dermatitis in children, is also associated with xerotic dermatitis and allergic contact dermatitis in adults. Bacterial infections rarely target vHFs, in contrast to tHFs. Trichodysplasia spinulosa (TdS) links to TdS-associated polyomavirus infection localized to the inner root sheath cells of vHFs, underdiagnosed in immunocompromised patients. The varying manifestation and pathogenic significance of Malassezia furfur in Malassezia (pityrosporum) folliculitis, pityriasis versicolor, and seborrheic dermatitis remain debated. Proliferative/neoplastic entities of vHFs include vellus hair cyst, pilomatrixoma, trichoepithelioma, and trichostasis spinulosa. Follicular spiny hyperkeratosis, lichen spinulosus, and lichen scrofulosorum are reactive conditions of vHFs. Recognizing vHF-associated diseases helps us to better understand the human hair follicles and to enhance daily dermatological practices.